Single fiber EMG as a prognostic tool in myasthenia gravis. Issue 6 (11th October 2016) - Baruca, Mateja; Leonardis, Lea; Podnar, Simon; Hojs‐Fabjan, Tanja; Grad, Anton; Jerin, Aleš; Blagus, Rok; Šega‐Jazbec, Saša
ABSTRACT: Introduction : Single fiber electromyography (SFEMG) is the most sensitive diagnostic tool for diagnosis of myasthenia gravis (MG). Its prognostic value is not known. Methods : We retrospectively analyzed the clinical course of 232 MG patients who presented with only mild symptoms and had SFEMG of the orbicularis oculi muscle. We correlated their SFEMG results with the severity of their later clinical course. Results : During the observation period 39 patients (17%) developed severe disease exacerbations, and 193 (83%) remained stable. Patients with severe disease exacerbation had a significantly higher mean jitter value ( P < 0.0001), a greater percentage of fibers with increased jitter ( P < 0.0001), and/or impulse blocking ( P < 0.0001) on SFEMG. Conclusions : The extent of the SFEMG abnormalities in this study correlated with the later clinical course of MG. Muscle Nerve 54 : 1034–1040, 2016